E-cigarette or vaping use-associated lung injury - M. А Karpenko; D. Yu. Ovsyannikov; P. А. Frolov; T. I. Nikiforova; M. V. Khandy (Туберкулез и болезни лёгких)
This literature review presents data from 57 publications on vaping and e-cigarette-associated lung injury or EVALI (e-cigarette or vaping use-associated lung injury) that was first reported in 2019. The article describes the epidemiology of EVALI, the mechanism of injuring effects of vaping on the lungs, clinical signs, diagnosis and diagnostic criteria, therapy and subsequent management of patients with EVALI.